Amorphous boron nitride film and antireflection coating structure including the same

By using an amorphous boron nitride film formed by PECVD as an anti-reflective coating in display devices, the problems of reduced contrast and image overlap caused by external light reflection are solved, achieving a reduction in reflectivity and an improvement in image quality, and possessing excellent mechanical and chemical stability.

CN114578460BActive Publication Date: 2026-11-03SAMSUNG ELECTRONICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110799177.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-30
Filing Date
2021-07-15
Publication Date
2026-11-03
Estimated Expiration
2041-07-15

AI Technical Summary

Technical Problem

In display devices, existing technologies struggle to effectively address issues such as reduced contrast or image overlap caused by the reflection of external light.

Method used

Amorphous boron nitride film is used as an anti-reflection coating. The amorphous boron nitride film is formed on the substrate by PECVD. The amorphous boron nitride film has the characteristics of low refractive index, low dielectric constant and high density. The thickness is designed to be one-quarter of the incident light wavelength to reduce reflectivity.

Benefits of technology

It effectively reduces the reflectivity of display devices, improves contrast, and enhances the anti-reflective properties of devices due to the chemical and mechanical stability of the amorphous boron nitride film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114578460B_ABST
    Figure CN114578460B_ABST
Patent Text Reader

Abstract

An amorphous boron nitride film and an antireflective coating structure including the amorphous boron nitride film are provided. 3 Hybrid bonds and sp 2 The amorphous structure of hybridized bonds, wherein sp in the amorphous boron nitride film 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds is less than about 20%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications

[0002] This application is based on and claims priority to Korean Patent Application No. 10-2020-0165074, filed with the Korean Intellectual Property Office on November 30, 2020, the entire disclosure of which is incorporated herein by reference. Technical Field

[0003] This disclosure relates to amorphous boron nitride films and antireflective coating structures including the same. Background Technology

[0004] In display devices such as liquid crystal display (LCD) devices or organic light-emitting diode (OLED) devices, problems such as reduced contrast or image overlap may occur due to the reflection of external light, and therefore, in order to solve this problem, it may be necessary to provide an anti-reflective film. Summary of the Invention

[0005] Amorphous boron nitride films and antireflective coating structures including them are provided.

[0006] Other aspects will be set forth in part in the description which follows, and in part will be apparent from the description, or may be learned by practice of the embodiments presented in this disclosure.

[0007] In an embodiment, the amorphous boron nitride film has an amorphous structure, said amorphous structure comprising sp 3 Hybrid bonds and sp 2 Hybrid bonds. The sp bonds in the amorphous boron nitride film. 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds can be less than about 20%.

[0008] In some embodiments, the amorphous boron nitride film may have a refractive index of about 1.0 to about 1.5 for light in the wavelength range of about 100 nm to about 1000 nm.

[0009] In some embodiments, the atomic ratio of boron to nitrogen in the amorphous boron nitride film may be from about 0.5 to about 2.0.

[0010] In some embodiments, the surface roughness of the amorphous boron nitride film may be about 0.5 rms (root mean square) or less.

[0011] In some embodiments, the dielectric constant of the amorphous boron nitride film may be about 2.5 or less.

[0012] In some embodiments, the band gap of the amorphous boron nitride film may be about 6.0 eV or less.

[0013] In some embodiments, the density of the amorphous boron nitride film can be approximately 1.8 g / cm³. 3 Or larger.

[0014] In some embodiments, the hydrogen content of the amorphous boron nitride film may be less than about 10 atoms.

[0015] In one embodiment, the antireflective coating structure includes: a substrate (base plate, substrate), and an amorphous boron nitride film having an amorphous structure on the substrate. The amorphous structure may include sp 3 Hybrid bonds and sp 2 Hybrid bonds. The sp bonds in the amorphous boron nitride film. 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds can be less than about 20%.

[0016] In some embodiments, the amorphous boron nitride film may have a refractive index of about 1.0 to about 1.5 for light in the wavelength range of about 100 nm to about 1000 nm.

[0017] In some embodiments, the thickness of the amorphous boron nitride film may be 1 / 4 of the center wavelength of the light incident on the amorphous boron nitride film.

[0018] In some embodiments, the density of the amorphous boron nitride film may be approximately 1.8 g / cm³. 3 Or larger.

[0019] In some embodiments, the antireflective coating structure may further include at least one material layer provided (disposed) between the substrate and the amorphous boron nitride film. The at least one material layer may have a refractive index greater than that of the amorphous boron nitride film.

[0020] In one embodiment, the image sensor may include: a substrate, a plurality of photodiodes in a two-dimensional form on the substrate, a color filter layer on the plurality of photodiodes, and an amorphous boron nitride film having an amorphous structure on the plurality of photodiodes. The amorphous structure may include sp 3 Hybrid bonds and sp 2 Hybrid bonds. The sp bonds in the amorphous boron nitride film. 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds can be less than about 20%.

[0021] In some embodiments, the amorphous boron nitride film may be located between the plurality of photodiodes and the color filter layer.

[0022] In some embodiments, the amorphous boron nitride film may have a refractive index of about 1.0 to about 1.5 for light in the wavelength range of about 100 nm to about 1000 nm.

[0023] In some embodiments, the image sensor may further include a plurality of microlenses in two-dimensional form on the color filter layer.

[0024] In one embodiment, the lithographic device may include: a substrate, a photoresist layer on the substrate, and an amorphous boron nitride film having an amorphous structure between the substrate and the photoresist layer. The amorphous structure may include sp 3 Hybrid bonds and sp 2 Hybrid bonds. The sp bonds in the amorphous boron nitride film. 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds can be less than about 20%.

[0025] In some embodiments, the amorphous boron nitride film may have a refractive index of about 1.0 to about 1.5 for light in the wavelength range of about 100 nm to about 1000 nm.

[0026] In some embodiments, the surface roughness of the amorphous boron nitride film may be about 0.5 rms or less.

[0027] In one embodiment, the solar cell may include: a light-absorbing layer that absorbs incident light and generates electrical energy, and an amorphous boron nitride film having an amorphous structure on the light-absorbing layer. The amorphous structure may include sp 3 Hybrid bonds and sp 2 Hybrid bonds. The sp bonds in the amorphous boron nitride film. 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds can be less than about 20%.

[0028] In some embodiments, the amorphous boron nitride film may have a refractive index of about 1.0 to about 1.5 for light in the wavelength range of about 100 nm to about 1000 nm.

[0029] In some embodiments, the solar cell may further include a heat dissipation layer between the light-absorbing layer and the amorphous boron nitride film.

[0030] In one embodiment, the display device may include: a display panel, and an amorphous boron nitride film on the display panel having an amorphous structure, the amorphous structure comprising sp 3 Hybrid bonds and sp 2Hybridized bonds, wherein sp in the amorphous boron nitride film 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds can be less than about 20%.

[0031] In some embodiments, the amorphous boron nitride film may have a refractive index of about 1.0 to about 1.5 for light in the wavelength range of about 100 nm to about 1000 nm.

[0032] In some embodiments, the display device may further include a protective film between the display panel and the amorphous boron nitride film. The protective film may have a refractive index greater than that of the amorphous boron nitride film. Attached Figure Description

[0033] The above and other aspects, features, and advantages of certain embodiments of this disclosure will become more apparent from the following description taken in conjunction with the accompanying drawings, wherein:

[0034] Figure 1 A diagram of an anti-reflective coating structure according to one embodiment;

[0035] Figure 2A-2C A diagram illustrating a method for forming an amorphous boron nitride film according to an embodiment;

[0036] Figure 3A and 3B The images show TEM images and diffraction patterns of amorphous boron nitride films, respectively, based on transmission electron microscopy (TEM) analysis.

[0037] Figure 4A and 4B The images show TEM images and diffraction patterns of the nanocrystalline boron nitride film, respectively, based on TEM analysis results.

[0038] Figure 5 The images show the Raman spectra of crystalline boron nitride films, nanocrystalline boron nitride films, and amorphous boron nitride films.

[0039] Figure 6 The figures show the Fourier transform infrared (FT-IR) spectra of amorphous boron nitride films and nanocrystalline boron nitride films.

[0040] Figure 7A and 7B The figures are X-ray photoelectron spectroscopy (XPS) curves for amorphous boron nitride films and nanocrystalline boron nitride films, respectively.

[0041] Figure 8 A graph showing the measured dielectric constants of amorphous boron nitride films and nanocrystalline boron nitride films;

[0042] Figure 9 A graph showing the simulation results of the density of the amorphous boron nitride film;

[0043] Figure 10 A graph showing the relationship between dielectric constant and density for various materials;

[0044] Figure 11 A graph showing the relationship between the dielectric constant and the breakdown field (breakdown electric field) of various materials;

[0045] Figure 12 A graph showing the breakdown bias of an amorphous boron nitride film at different temperatures;

[0046] Figure 13 The image shows the FT-IR spectrum of the amorphous boron nitride film.

[0047] Figure 14A Figure showing the analytical results of high-resolution Rutherford backscattering spectroscopy (HR-RBS) for amorphous boron nitride films;

[0048] Figure 14B Figure showing the results of high-resolution elastic recoil detection analysis (HR-ERDA) of amorphous boron nitride films;

[0049] Figure 15 The graph shows the absorption of crystalline boron nitride films, nanocrystalline boron nitride films, and amorphous boron nitride films according to the wavelength of light.

[0050] Figure 16 Figure showing the results of near-edge X-ray absorption fine structure (NEXAFS) analysis of amorphous boron nitride films;

[0051] Figure 17A and 17B The figures show the Raman spectra and XPS analysis results of the amorphous boron nitride films transferred to the substrate, respectively.

[0052] Figure 18 A diagram of an anti-reflective coating structure according to another embodiment;

[0053] Figure 19 A diagram of an image sensor according to an embodiment;

[0054] Figure 20 A diagram of a photolithography apparatus according to an embodiment;

[0055] Figure 21 A diagram of a solar cell according to an embodiment; and

[0056] Figure 22 This is a diagram of a display device according to an embodiment. Detailed Implementation

[0057] The embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals always refer to the same elements. In this respect, the embodiments may take different forms and should not be construed as limited to the description set forth herein. Therefore, the embodiments are described below only by reference to the accompanying drawings to illustrate aspects. As used herein, the term "and / or" includes any and all combinations of one or more of the associated enumerated items. Expressions such as "at least one of" modify the entire list of elements when preceding or following it, without modifying any individual element of the list.

[0058] For ease of explanation and clarity, the thickness or dimensions of each layer shown in the figures may be enlarged. In this respect, this embodiment may take different forms and should not be construed as limited to the description set forth herein. Therefore, embodiments are described below only with reference to the accompanying drawings to illustrate aspects of this description.

[0059] In the layered structure described below, when a component is positioned "above" or "on top of" another component, the component may include not only elements that are in direct contact with the upper / lower / left / right side of the other component, but also elements that are positioned non-contactly above / below / left / right of the other component. Singular expressions in the specification include plural expressions unless clearly stated otherwise in the context. It will be further understood that the terms "comprising" and / or "including" as used herein indicate the presence of the stated features or components, but do not exclude the presence or addition of one or more additional features or components.

[0060] As used herein, the singular forms “a” (indefinite articles “a”, “an”) and “the” are intended to include the plural forms as well, unless the context clearly indicates otherwise. Furthermore, the steps of all methods described herein can be performed in any suitable order, unless otherwise stated herein or unless clearly contradicted by the context. This disclosure is not limited to the order of the described steps.

[0061] Furthermore, terms such as “part,” “unit,” “module,” and “block” used in the specification may refer to a unit for performing at least one function or operation, and said unit may be equipped with hardware, software, or a combination of hardware and software.

[0062] Furthermore, the connecting lines or bodies shown in the figures are intended to represent functional relationships and / or physical or logical couplings (connections) between components. It should be noted that many alternative or additional functional relationships, physical connections, or logical connections may exist in actual devices.

[0063] Any and all instances or language (e.g., "for example") provided herein are intended only to better illustrate the contents of this disclosure and not to limit the scope of this disclosure, unless otherwise stated.

[0064] When the terms “about” or “substantially” are used in this specification to refer to numerical values, it is intended that the relevant numerical values ​​include manufacturing or operational tolerances (e.g., ±10%) surrounding the stated numerical values. Similarly, when the terms “generally” and “substantially” are used to refer to geometry, it is intended that the geometry does not require precision, but rather the flexibility of the shape within the scope of this disclosure. Furthermore, regardless of whether a numerical value or shape is modified by “about” or “substantially,” it will be understood that these values ​​and shapes should be interpreted as including manufacturing or operational tolerances (e.g., ±10%) surrounding the stated numerical values ​​or shapes.

[0065] As used in this article, the term "center wavelength" refers to the wavelength located in the middle of the wavelength range of light.

[0066] Figure 1 A diagram of an anti-reflective coating structure 100 according to an embodiment.

[0067] refer to Figure 1 The anti-reflective coating structure 100 may include a substrate 110 and an amorphous boron nitride film 120 provided on the substrate 110. The anti-reflective coating structure 100 may be used in various devices such as image sensors, photolithography equipment, solar cells, display devices, etc.

[0068] The substrate 110 can be an object that requires anti-reflective properties. The substrate 110 is supplied with an amorphous boron nitride film 120. The amorphous boron nitride film 120 can function as an anti-reflective film.

[0069] The following descriptions describe crystalline boron nitride films, nanocrystalline boron nitride films, and amorphous boron nitride films.

[0070] The crystalline boron nitride film may be a boron nitride film comprising grains having a size greater than 100 nm. The crystalline boron nitride film may include, for example, a hexagonal boron nitride film (h-BN) or a cubic boron nitride film (c-BN).

[0071] The nanocrystalline boron nitride film (nc-BN) may be a boron nitride film comprising grains having a size smaller than that of a crystalline boron nitride film. The nanocrystalline boron nitride film may comprise grains having a size of about 100 nm or smaller. Specifically, for example, the nanocrystalline boron nitride film may comprise grains having a size of about 0.5 nm to about 100 nm.

[0072] The amorphous boron nitride film (a-BN) 120 may be a boron nitride film with an amorphous structure. The amorphous boron nitride film 120 may include sp... 3Hybrid bonds and sp 2 Hybridized bonds, in which sp in amorphous boron nitride film 120 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds can be less than about 20%. The amorphous boron nitride film 120 may additionally include a small number of grains having a size of about a few nanometers, for example, about 3 nm or smaller.

[0073] In the amorphous boron nitride film 120, the atomic ratio of boron to nitrogen can be, for example, from about 0.5 to about 2.0. In a specific example, the atomic ratio of boron to nitrogen can be from about 0.9 to about 1.1. However, this disclosure is not limited thereto.

[0074] The amorphous boron nitride film 120 may further include hydrogen, but the hydrogen content may be relatively small. For example, the hydrogen content may be less than about 10 atomic percent. Because the hydrogen content in the amorphous boron nitride film 120 may be small, the amorphous boron nitride film 120 may be chemically stable.

[0075] The amorphous boron nitride film 120 may have a low refractive index. For example, the amorphous boron nitride film 120 may have a refractive index of about 1.0 to about 1.5 for light in the wavelength range of about 100 nm to about 1000 nm.

[0076] The amorphous boron nitride film 120 may have a low dielectric constant. For example, the dielectric constant of the amorphous boron nitride film 120 may be about 2.5 or less. More specifically, for example, the dielectric constant of the amorphous boron nitride film 120 may be from about 1.0 to about 2.5.

[0077] The amorphous boron nitride film 120 can have a high density. For example, the density of the amorphous boron nitride film 120 can be about 1.8 g / cm³. 3 Or even higher. Specifically, for example, the density of an amorphous boron nitride film 120 can be approximately 1.8 g / cm³. 3 Approximately 2.5 g / cm³ 3 Thus, since the amorphous boron nitride film 120 can have a high density, it can also have excellent mechanical properties.

[0078] The band gap of the amorphous boron nitride film 120 can be about 6.0 eV or less. In addition, the surface roughness of the amorphous boron nitride film 120 can be 0.5 root mean square (rms) or less.

[0079] Because the amorphous boron nitride film 120, as described above, has a low refractive index and excellent mechanical and chemical stability, the antireflective coating structure 100 can be implemented (realized) by using the amorphous boron nitride film 120 as an antireflective film.

[0080] The amorphous boron nitride film 120 can be formed to have a thickness t, which satisfies the condition of destructive interference of reflected light at the interface between air and the amorphous boron nitride film 120 to reduce reflectivity. For example, when the center wavelength of light incident on the antireflective coating structure 100 is λ, the amorphous boron nitride film 120 with a thickness of about λ / 4 can reduce reflectivity. In an example, when the incident light has a center wavelength of about 400 nm, the amorphous boron nitride film 120 can be formed on the substrate 110 with a thickness of about 100 nm, thereby reducing reflectivity. Furthermore, when the incident light has a wavelength range of about 300 nm to about 800 nm, since the center wavelength of the incident light is about 550 nm, the amorphous boron nitride film 120 can be formed on the substrate 110 with a thickness of about 135 nm to about 140 nm, thereby reducing reflectivity.

[0081] The following description describes a method for forming the aforementioned amorphous boron nitride film 120 using plasma-enhanced chemical vapor deposition (PECVD). Figure 2A-2C This is a diagram illustrating a method for forming an amorphous boron nitride film according to an embodiment.

[0082] refer to Figure 2A Substrate 210 is prepared in a process chamber (not shown). Substrate 210 may be prepared in... Figure 1 The anti-reflective coating structure 100 includes a substrate 110 whose light reflection is limited and / or prevented. In this case, the substrate 210 can be a structure used in various devices such as image sensors, lithography equipment, solar cells, display devices, etc.

[0083] Substrate 210 can be used for growth Figure 2C The substrate of the amorphous boron nitride film 220. In this case, the substrate 210 may include a variety of materials. For example, the substrate 210 may include at least one of a semiconductor material, an insulating material, or a metal. The semiconductor material may include a group IV semiconductor or a semiconductor compound. Group IV semiconductors may include, for example, Si, Ge, Sn, etc., but this disclosure is not limited thereto. The semiconductor compound may include a material obtained by combining at least two elements such as Si, Ge, C, Zn, Cd, Al, Ga, In, B, C, N, P, S, Se, As, Sb, or Te. However, this disclosure is not limited thereto.

[0084] The insulating material may include at least one oxide, nitride, carbide, or derivative thereof of, for example, Si, Ni, Al, W, Ru, Co, Mn, Ti, Ta, Au, Hf, Zr, Zn, Y, Cr, Cu, Mo, or Gd. Furthermore, the substrate 210 may further include, for example, N or F in its SiCOH-based composition, and may include pores to reduce the dielectric constant. The substrate 210 may further include dopants. However, the above-described materials of the substrate 210 are merely examples.

[0085] Before placing the substrate 210 in the process chamber, the substrate 210 can be pretreated. For example, the substrate 210 can be subjected to ultrasonic treatment by immersion in an organic solvent such as acetone, and then cleaned with isopropanol (IPA) and nitrogen. Carbon impurities remaining on the surface of the substrate 210 can be removed by plasma treatment with oxygen, hydrogen, NH3, etc. Furthermore, native oxides can be removed by immersing the substrate 210 in an HF solution, and residual HF solution can be removed using anhydrous ethanol and nitrogen.

[0086] The process temperature for growing the amorphous boron nitride film 220 can be lower than the temperature used in typical chemical vapor deposition (CVD) processes. The process temperature for growing the amorphous boron nitride film 220 can be about 400°C or lower. For example, the process temperature for growing the amorphous boron nitride film 220 can be from about 15°C to about 400°C, but this disclosure is not limited thereto. When the process temperature is above about 400°C and about 700°C or lower, nanocrystalline boron nitride films can be formed.

[0087] The process pressure used to grow the amorphous boron nitride film 220 can be about 10 millitors or higher. For example, the process pressure used to grow the amorphous boron nitride film 220 can be from about 10 millitors to about 1 tor.

[0088] Next, a reaction gas for growing the amorphous boron nitride film 220 is injected into the process chamber. The reaction gas may include a boron nitride source for growing the amorphous boron nitride film 220.

[0089] The boron nitride source may be a source comprising both nitrogen and boron, such as cycloborazane (B3N3H6), ammonia-borane (NH3-BH3), etc. Furthermore, the boron nitride source may include a nitrogen source containing nitrogen and a boron source containing boron. The nitrogen source may include at least one of, for example, ammonia (NH3) or nitrogen gas (N2), and the boron source may include at least one of BH3, BF3, BCl3, B2H6, (CH3)3B, and (CH3CH2)3B.

[0090] The reactant gas may further include an inert gas. The inert gas may include at least one of, for example, argon, neon, nitrogen, helium, krypton, or xenon. Furthermore, the reactant gas may further include hydrogen to facilitate activation via plasma. Figure 2A An example is shown in which boron nitride source (B3N3H6) is used and argon is used as the inert gas.

[0091] The mixing ratio of the reactant gases in the injection process chamber can be adjusted by controlling the flow rates of the boron nitride source, inert gas, and hydrogen in the injection process chamber. To form the amorphous boron nitride film 220, the content of the boron nitride source in the reactant gases needs to be relatively low. Therefore, the flow rate of the boron nitride source introduced into the process chamber can be relatively low.

[0092] The volume ratio of boron nitride source and inert gas injected into the process chamber to form amorphous boron nitride film 220 can be, for example, about 1:(10-5000), and the volume ratio of boron nitride source, inert gas and hydrogen can be, for example, about 1:(10-5000):(10-500).

[0093] Thus, since the volume ratio of the boron nitride source in the reaction gas is small, an amorphous boron nitride film 220 with almost no crystallinity (i.e., crystallinity almost 0) can be formed on the surface of the substrate 210.

[0094] When an excess of boron nitride source is supplied to the process chamber, the amorphous boron nitride film 220 can grow irregularly and precursor adsorption can occur. To limit and / or prevent these problems, the flow rate of the boron nitride source can be low. For example, the flow rate of the boron nitride source can be about 0.05 standard cubic centimeters (sccm), and the flow rate of the inert gas can be about 50 sccm, but this disclosure is not limited thereto. Furthermore, the flow rate of hydrogen can be about 50 sccm or greater, but this disclosure is not limited thereto.

[0095] During the introduction of the reactive gas into the process chamber, plasma can be generated in the process chamber using a plasma device. The power used to generate the plasma can be, for example, from about 10W to about 4000W. In a specific example, the power used to generate the plasma can be about 60W, but this disclosure is not limited thereto.

[0096] The plasma device may be an apparatus that provides inductively coupled plasma (ICP), microwave plasma, capacitively coupled discharge plasma, electron cyclotron resonance (ECR) plasma, spiral wave plasma, etc., but this disclosure is not limited thereto. When power for generating plasma is applied from the plasma device to the process chamber, an electric field is induced in the process chamber, and the induced electric field can be used to generate plasma for growing amorphous boron nitride film 220.

[0097] refer to Figure 2B Nitrogen and boron atoms can be activated by a plasma containing a reaction gas mixture of the boron nitride source, an inert gas, and hydrogen, and the activated nitrogen atoms (N*) and activated boron atoms (B*) can be adsorbed onto the surface of the substrate 210. Since the plasma of the inert gas continuously induces activation of the substrate 210, the adsorption of activated nitrogen (N*) and activated boron (B*) on the surface of the substrate 210 can be accelerated.

[0098] refer to Figure 2C Because the adsorption of activated nitrogen (N*) and activated boron (B*) on the surface of substrate 210 is accelerated, an amorphous boron nitride film 220 can be grown on the surface of substrate 210. Since relatively low amounts of activated nitrogen (N*) and activated boron (B*) are adsorbed on the surface of substrate 210 at low temperatures, i.e., 400°C or lower, an amorphous boron nitride film 220 with almost no crystallinity can be grown to form on the surface of substrate 210.

[0099] Although the case in which the amorphous boron nitride film 220 is grown directly on the substrate 210 is described, the amorphous boron nitride film 220 formed on the substrate 210 can be separated from the substrate 210 and transferred to another substrate or device.

[0100] The amorphous boron nitride film 220 formed by the above method has a composition including sp 3 Hybrid bonds and sp 2 The amorphous structure of hybridized bonds, wherein sp in the amorphous boron nitride film 220 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds can be less than about 20%. The sp content in the amorphous boron nitride film 220 can be measured by, for example, X-ray photoelectron spectroscopy (XPS). 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds. The amorphous boron nitride film 220 may additionally include grains having a size of a few nanometers, for example, about 3 nm or smaller.

[0101] Nanocrystalline boron nitride films can be formed by changing the process conditions, such as process temperature and process pressure, during the formation of the amorphous boron nitride film 220 described above. The nanocrystalline boron nitride film may include grains with a size of about 100 nm or smaller.

[0102] In the amorphous boron nitride film 220, the atomic ratio of boron to nitrogen can be, for example, from about 0.5 to about 2.0. In a specific example, the atomic ratio of boron to nitrogen can be from about 0.9 to about 1.1. Furthermore, the amorphous boron nitride film 220 may further include hydrogen. In this case, the hydrogen content can be, for example, less than about 10 atomic%.

[0103] The amorphous boron nitride film 220 may have a low refractive index of about 1.0 to about 1.5 for light in the wavelength range of about 100 nm to about 1000 nm. Furthermore, the amorphous boron nitride film 220 may have a low dielectric constant of about 2.5 or less. Specifically, for example, the dielectric constant of the amorphous boron nitride film 220 may be about 1.0 to about 2.5.

[0104] Amorphous boron nitride films 220 can have a density of approximately 1.8 g / cm³. 3 Or even higher densities. Amorphous boron nitride film 220 may have a surface roughness of about 0.5 rms or less. Amorphous boron nitride film 220 may have a band gap of about 6.0 eV or less.

[0105] The aforementioned amorphous boron nitride film 220 can serve the following functions: Figure 1 The function of the antireflective film shown is illustrated. The device can be manufactured by forming an additional layer on the amorphous boron nitride film 220. Furthermore, the amorphous boron nitride film 220 can be separated from the substrate 210 for transfer to another substrate or device, and it can function as an antireflective film.

[0106] Table 1 shows example test results comparing the properties of crystalline boron nitride films (specifically, hexagonal boron nitride films (h-BN)), nanocrystalline boron nitride films (nc-BN), and amorphous boron nitride films (a-BN).

[0107] [Table 1]

[0108]

[0109]

[0110] Referring to Table 1, it can be seen that the refractive index of amorphous boron nitride (a-BN) film for light at a wavelength of 633 nm is lower than that of crystalline boron nitride (h-BN) film and nanocrystalline boron nitride (nc-BN) film. The refractive index of amorphous boron nitride (a-BN) film can be almost similar to that of air. Furthermore, it can be seen that amorphous boron nitride (a-BN) film has excellent mechanical inertia (stability) because it has a higher density than crystalline boron nitride (h-BN) film. Amorphous boron nitride film has a lower dielectric constant than crystalline boron nitride (h-BN) film and nanocrystalline boron nitride (nc-BN) film.

[0111] It can be seen that the hexagonal boron nitride film (h-BN) has a band gap of approximately 6.05 eV, the amorphous boron nitride film (a-BN) has a band gap of approximately 5.96 eV, and the nanocrystalline boron nitride film (nc-BN) has a band gap of approximately 5.85 eV. In other words, the amorphous boron nitride film (a-BN) and the nanocrystalline boron nitride film (nc-BN) have lower band gaps than the hexagonal boron nitride film (h-BN). Therefore, it can be seen that the amorphous boron nitride film (a-BN) is chemically stable.

[0112] Table 2 below shows example test results comparing the properties of SiO2, low refractive index polymers (low RI polymers), MgF2, and amorphous boron nitride films (a-BN).

[0113] [Table 2]

[0114]

[0115] Referring to Table 2, amorphous boron nitride (a-BN) films have a lower refractive index than SiO2 and low-refractive-index polymers. Furthermore, it can be seen that amorphous boron nitride (a-BN) films exhibit excellent mechanical inertness due to their higher density and harderness compared to low-refractive-index polymers. Although MgF2 has a low refractive index and high density, it requires a passivation film due to its oxidation and low chemical inertness.

[0116] As described above, it can be seen that amorphous boron nitride (a-BN) films have a low refractive index similar to air and excellent mechanical inertness due to their high density and high hardness. Furthermore, amorphous boron nitride (a-BN) films exhibit excellent adhesion to additional layers and also possess excellent thermal and chemical inertness. Amorphous boron nitride (a-BN) films have high transmittance in the visible or ultraviolet light range and also exhibit excellent diffusion-blocking properties. Since amorphous boron nitride (a-BN) films can have a surface roughness of about 0.5 rms or less, their surface can be formed very uniformly.

[0117] The following description details the analytical results of the measurement characteristics of the amorphous boron nitride film (a-BN) according to the embodiments. In the following figures, "a-BN" represents the measurement results of the amorphous boron nitride film (specifically, hexagonal boron nitride film) formed by inductively coupled plasma chemical vapor deposition (ICP-CVD) at a process temperature of 400°C, and "nc-BN" represents the measurement results of the nanocrystalline boron nitride film formed by ICP-CVD at a process temperature of 700°C.

[0118] Figure 3A and 3B TEM images and diffraction patterns of the amorphous boron nitride film (a-BN) based on transmission electron microscopy (TEM) analysis are shown. Figure 3A The TEM images show that the atoms constituting the amorphous boron nitride film (a-BN) are arranged randomly, and Figure 3B The diffraction pattern is a typical diffuse diffraction pattern of amorphous films.

[0119] Figure 4A and Figure 4B This is a TEM image and diffraction pattern of the nanocrystalline boron nitride film (nc-BN) based on TEM analysis results. Figure 4A and 4B The results show that nano-sized grains are arranged in the nanocrystalline boron nitride film (nc-BN). Therefore, it can be seen that the nanocrystalline boron nitride film (nc-BN) can be formed at a process temperature of 700°C, which is above 400°C.

[0120] Figure 5 The images show the Raman spectra of crystalline boron nitride (tri-hBN), nanocrystalline boron nitride (nc-BN), and amorphous boron nitride (a-BN). Figure 5 In this text, "SiO2 / Si" indicates the Raman spectrum of a SiO2 / Si substrate, and "a-BN" indicates the Raman spectrum measured after forming an amorphous boron nitride film (a-BN) on a SiO2 / Si substrate at a processing temperature of 400℃. "nc-BN" indicates the Raman spectrum measured after forming a nanocrystalline boron nitride film (nc-BN) on a SiO2 / Si substrate at a processing temperature of 700℃, and "tri-hBN" indicates the Raman spectrum measured after epitaxially growing a three-layer hexagonal boron nitride film (h-BN) on a SiO2 / Si substrate.

[0121] refer to Figure 5 It can be seen that in the Raman spectra of hexagonal boron nitride films (tri-hBN) and nanocrystalline boron nitride films (nc-BN), at approximately 1370 cm⁻¹... -1A peak is present at the point, and therefore, the hexagonal boron nitride film (tri-hBN) and the nanocrystalline boron nitride film (nc-BN) have crystallinity (i.e., crystallinity greater than 0). Conversely, it can be seen that no peak is present in the Raman spectrum of the amorphous boron nitride film (a-BN), and therefore, the amorphous boron nitride film (a-BN) has no crystallinity (i.e., crystallinity is 0).

[0122] Figure 6 The image shows the Fourier transform infrared (FT-IR) spectra of the amorphous boron nitride film (a-BN) and the nanocrystalline boron nitride film (nc-BN). Figure 6 The FT-IR spectrum measured using s-polarized light at an incident angle of 60° is shown.

[0123] refer to Figure 6 It can be seen that in the FT-IR spectrum of the amorphous boron nitride film (a-BN), at 1370 cm⁻¹... -1 There is an absorption peak nearby due to the transverse optical mode, and at 1570 cm⁻¹ -1 Another absorption peak is present nearby. This means that the amorphous boron nitride film (a-BN) has amorphous properties.

[0124] It can be seen that in the FT-IR spectrum of the nanocrystalline boron nitride film (nc-BN), at 1370 cm⁻¹... -1 There is an absorption peak nearby due to the transverse optical mode, but at 1570 cm⁻¹... -1 There are no absorption peaks in the vicinity. This means that the nanocrystalline boron nitride film (nc-BN) does not have amorphous properties.

[0125] Figure 7A X-ray photoelectron spectroscopy (XPS) curves for the amorphous boron nitride film (a-BN) are shown. Figure 7B XPS curves for the nanocrystalline boron nitride film (nc-BN) are shown.

[0126] It can be seen that, Figure 7A In the XPS curves, the 1-s peak for boron is 190.3 eV, and the 1-s peak for nitrogen is 397.9 eV. It can be seen that, based on the peak sizes of boron and nitrogen, the atomic ratio of boron to nitrogen in the amorphous boron nitride film (a-BN) is approximately 1:1.08. The amorphous boron nitride film (a-BN) may include sp... 3 Hybrid bonds and sp 2 Hybridized bonds, wherein sp in the amorphous boron nitride film 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds can be less than about 20%.

[0127] It can be seen that, Figure 7B In the XPS curves, the 1-s peak for boron is 190.3 eV, and the 1-s peak for nitrogen is 397.9 eV. It can be seen that the 1-s peaks for boron and nitrogen in the nanocrystalline boron nitride film (nc-BN) almost match those in the amorphous boron nitride film (a-BN). Therefore, it can be seen that the atomic ratio of boron to nitrogen in the nanocrystalline boron nitride film (nc-BN) is approximately 1:1.08.

[0128] Figure 8 A graph showing the measured dielectric constant (specifically, relative dielectric constant) of the amorphous boron nitride film (a-BN) and the nanocrystalline boron nitride film (nc-BN). Figure 8 The results of 50 or more dielectric constant measurements are shown, with the thick line representing the average dielectric constant.

[0129] refer to Figure 8 The dielectric constant of the amorphous boron nitride film (a-BN) is inversely proportional to the operating frequency. It can be seen that at an operating frequency of 100 kHz, the average dielectric constant of the amorphous boron nitride film (a-BN) is approximately 1.78. It can also be seen that at an operating frequency of 1 MHz, the average dielectric constant of the amorphous boron nitride film (a-BN) is approximately 1.16, which is close to the dielectric constant of air or vacuum. Thus, the low dielectric constant of the amorphous boron nitride film (a-BN) is caused by the nonpolar bonding between boron and nitrogen atoms. The dielectric constant can be further reduced by forming pores in the amorphous boron nitride film (a-BN).

[0130] It can be seen that, in the operating frequency range of approximately 50 kHz to approximately 1 MHz, the average dielectric constant of the nanocrystalline boron nitride film (nc-BN) is approximately 2.5 or less. For example, the average dielectric constant of the nanocrystalline boron nitride film (nc-BN) can be approximately 2.3 to approximately 2.5. In the operating frequency range of approximately 50 kHz to approximately 1 MHz, the average dielectric constant of the hexagonal boron nitride film (h-BN) has been measured to be approximately 2.9 to approximately 3.8.

[0131] Figure 9 This is a graph showing the simulation results of the density of the amorphous boron nitride film (a-BN). The simulation results show the mass density of the amorphous boron nitride film (a-BN) along the thickness direction after growing a 40 nm thick amorphous boron nitride film (a-BN) on a Si substrate.

[0132] refer to Figure 9 It can be seen that the mass density of the amorphous boron nitride film (a-BN) is approximately 2 g / cm³. 3As can be seen from the following description, although the dielectric constant of the amorphous boron nitride film (a-BN) is low, its high density ensures that its mechanical strength is not reduced.

[0133] Figure 10 This is a graph showing the relationship between dielectric constant and density for various materials.

[0134] refer to Figure 10 The dielectric constant and density of most materials are proportional to each other. Therefore, materials with low dielectric constants typically have low densities, and consequently, low mechanical strength. However, the amorphous boron nitride film (a-BN) exhibits approximately 2 g / cm³ density when its dielectric constant is approximately 2. 3 The density of the amorphous boron nitride film (a-BN) is relatively high. Therefore, the amorphous boron nitride film (a-BN) can have high mechanical strength while possessing a low dielectric constant, because its density is relatively high compared to other materials.

[0135] Figure 11 This is a graph showing the relationship between the dielectric constant and the breakdown field in various materials.

[0136] refer to Figure 11 It can be seen that the dielectric constant and the breakdown field are proportional to each other. It can also be seen that the breakdown field of the amorphous boron nitride film (a-BN) is higher than that of other materials with a dielectric constant close to 2.

[0137] Table 3 below shows the example test results of the dielectric constant and breakdown field of the amorphous boron nitride film (a-BN) and the hexagonal boron nitride film (h-BN).

[0138] [Table 3]

[0139]

[0140] Referring to Table 3, it can be seen that, since the dielectric constant of the amorphous boron nitride film (a-BN) is less than or equal to 2 at operating frequencies of approximately 100 kHz and approximately 1 MHz, the dielectric constant of the amorphous boron nitride film (a-BN) is less than that of the hexagonal boron nitride film (h-BN). Furthermore, it can be seen that, since the breakdown field of the amorphous boron nitride film (a-BN) is approximately 7.3 MV / cm, the breakdown field of the amorphous boron nitride film (a-BN) is much larger than that of the hexagonal boron nitride film (h-BN).

[0141] Figure 12 This is a graph showing the breakdown bias of the amorphous boron nitride film (a-BN) at temperature. Figure 12In this context, "Co / a-BN / Si" indicates that an amorphous boron nitride film (a-BN) and a Co layer are sequentially deposited on a Si substrate, and "Co / TiN / S" indicates that a TiN layer and a Co layer are sequentially deposited on a Si substrate.

[0142] refer to Figure 12 It can be seen that the breakdown bias voltage of the amorphous boron nitride film (a-BN) is inversely proportional to temperature. It can also be seen that even when the breakdown voltage decreases with increasing temperature, the breakdown bias voltage of the amorphous boron nitride film (a-BN) is still greater than that of the TiN layer. This means that the amorphous boron nitride film (a-BN) is stable at various temperatures.

[0143] Figure 13 This is a graph showing the FT-IR spectrum of the amorphous boron nitride film (a-BN). (Reference) Figure 13 It can be seen that there are no hydrogen-related bonds in the FT-IR spectrum of the amorphous boron nitride film (a-BN), because no peaks were observed at the wavenumbers corresponding to the BH and NH bonds.

[0144] Figure 14A The figure shows the analytical results of the amorphous boron nitride film (a-BN) by high-resolution Rutherford backscattering spectroscopy (HR-RBS). Figure 14B The figure shows the results of high-resolution elastic recoil detection analysis (HR-ERDA) of the amorphous boron nitride film (a-BN).

[0145] Figure 14A Measurement results are shown in the binding energy range from approximately 240 keV to approximately 400 keV, and Figure 14B Measurements are shown in the binding energy range of approximately 52 keV to approximately 68 keV. (Reference) Figure 14A and 14B As can be seen, Si and O, the elements that form the substrate, were measured, and B and N, the elements that form the amorphous boron nitride film (a-BN), were measured. Furthermore, hydrogen was also measured.

[0146] Table 4 below shows the usage Figure 14A and 14B The composition ratio of the amorphous boron nitride film (a-BN) calculated from the measurement results shown in the figure is as follows.

[0147] [Table 4]

[0148] B (atomic percentage) N (atomic percentage) H (atomic percentage) a-BN 47.6 46.9 5.5

[0149] Referring to Table 4, it can be seen that the ratio of boron to nitrogen is approximately 1.04:1. Furthermore, it can be seen that the hydrogen content in the amorphous boron nitride film (a-BN) is approximately 5.5 atomic%.

[0150] Figure 15 The graph shows the absorption of the crystalline boron nitride film (h-BN), the nanocrystalline boron nitride film (nc-BN), and the amorphous boron nitride film (a-BN) according to the wavelength of light. Figure 15 The absorption of light in the ultraviolet wavelength range is shown.

[0151] refer to Figure 15 As can be seen, although the crystalline boron nitride film (h-BN) and the nanocrystalline boron nitride film (nc-BN) each have high absorption for light at a wavelength of about 200 nm, the amorphous boron nitride film (a-BN) exhibits high transmittance due to its low absorption for light at a wavelength of about 200 nm.

[0152] Figure 16 Figure showing the results of near-edge X-ray absorption fine structure (NEXAFS) analysis of the amorphous boron nitride film (a-BN). Reference Figure 16 It can be seen that in the amorphous boron nitride film (a-BN), through sp 2 The BN plane formed by hybrid bonds is randomly oriented (oriented) in any direction.

[0153] Figure 17A and 17B Raman spectra and XPS images of the amorphous boron nitride film (a-BN) transferred to the substrate are shown, respectively.

[0154] Figure 17A Raman spectra of an amorphous boron nitride film (a-BN) transferred to a SiO2 substrate are shown. Figure 17A In this context, "bare SiO2" refers to the Raman spectrum of a SiO2 substrate where no amorphous boron nitride film (a-BN) has been grown, and "a-BN film" refers to the Raman spectrum of an amorphous boron nitride film (a-BN) transferred to the SiO2 substrate. The amorphous boron nitride film (a-BN) is grown on a copper foil (Cu foil) by inductively coupled plasma chemical vapor deposition (ICP-CVD) at a plasma power of approximately 30 W and a process temperature of approximately 300 °C, and then transferred to the SiO2 substrate. (Reference) Figure 17A As can be seen, the Raman spectra of the amorphous boron nitride film (a-BN) transferred to the SiO2 substrate are similar to those of the SiO2 substrate where no amorphous boron nitride film (a-BN) has grown. This indicates that the amorphous boron nitride film (a-BN) transferred to SiO2 has an amorphous structure similar to that of the SiO2 substrate.

[0155] Figure 17B XPS image of an amorphous boron nitride film (a-BN) transferred to a SiO2 substrate. Reference Figure 17BAs can be seen, in the amorphous boron nitride film (a-BN) transferred to the SiO2 substrate, similar to the amorphous boron nitride film (a-BN) grown at a process temperature of 400°C as described above, the 1-s peak for boron is approximately 190.3 eV, and the 1-s peak for nitrogen is approximately 397.9 eV. From the above, it can be seen that the atomic ratio of boron to nitrogen is approximately 1:1.08, and there are sp values ​​based on the respective peak sizes of boron and nitrogen. 2 key.

[0156] As described above, due to the low refractive index and excellent thermal, mechanical and chemical stability of the amorphous boron nitride film (a-BN), various devices can be implemented using the amorphous boron nitride film (a-BN) as an anti-reflective coating, as described below.

[0157] Figure 18 A diagram of an anti-reflective coating structure 300 according to another embodiment.

[0158] refer to Figure 18 The antireflective coating structure 300 may include a substrate 310, an amorphous boron nitride film 320, a first material layer 330, and a second material layer 340. The first and second material layers 330 and 340 are provided between the substrate 310 and the amorphous boron nitride film 320. Specifically, the second material layer 340 is provided on the upper surface of the substrate 310, and the first material layer 330 is provided on the upper surface of the second material layer 340. The amorphous boron nitride film 320 is provided on the upper surface of the first material layer 330. The amorphous boron nitride film 320 is the same as the amorphous boron nitride film described above, and therefore its description is omitted.

[0159] The first and second material layers 330 and 340 may comprise materials having a higher refractive index than the amorphous boron nitride film 320. The first material layer 330 may comprise materials having a higher refractive index than the second material layer 340.

[0160] In the wavelength range of about 100 nm to about 1000 nm, the amorphous boron nitride film 320 may have a refractive index of about 1.0 to about 1.5. The first material layer 330 may have a refractive index of, for example, about 2.0 to about 2.3, and the second material layer 340 may have a refractive index of, for example, about 1.5 to about 1.8. However, this disclosure is not limited thereto.

[0161] The first material layer 330 may include, for example, ZrO2, and the second material layer 340 may include, for example, CeF3 or AlO2. x However, this is merely an example, and the first and second material layers 330 and 340 may each comprise a variety of other materials.

[0162] The amorphous boron nitride film 320 and the first and second material layers 330 and 340 may each have a thickness for reducing reflectivity. For example, when the center wavelength of light incident on the antireflective structure 300 is λ, the amorphous boron nitride film 320 is formed to have a thickness of about λ / 4, the first material layer 330 is formed to have a thickness of about λ / 2, and the second material layer 340 is formed to have a thickness of about λ / 4, thereby reducing reflectivity.

[0163] Although the above description illustrates an example where two material layers (330 and 340) are provided between the substrate 310 and the amorphous boron nitride film 320, the present disclosure is not limited thereto, and one or three or more material layers may be provided between the substrate 310 and the amorphous boron nitride film 320.

[0164] Figure 19 This is a diagram of an image sensor 400 according to an embodiment. Figure 19 In this context, the image sensor 400 may be, for example, a complementary metal-oxide-semiconductor (CMOS) image sensor.

[0165] refer to Figure 19 The image sensor 400 may include a substrate 410, a plurality of photodiodes 450 provided on the substrate 410, an amorphous boron nitride film 420 provided on the photodiodes 450, and a color filter layer 460 provided on the amorphous boron nitride film 420.

[0166] Photodiodes 450 corresponding to pixels can be arranged in a two-dimensional form on substrate 410. A black matrix 455 can be provided between photodiodes 450. Photodiodes 450 can convert incident light into electrical energy, and metal wiring (not shown) for detecting the electrical energy generated from photodiodes 450 can be provided on substrate 410. Color filter layer 460 may include a plurality of color filters 460R, 460G, and 460B provided corresponding to photodiodes 450. Color filters 460R, 460G, and 460B can be, for example, a red color filter 460R, a green color filter 460G, and a blue color filter 460B. However, this disclosure is not limited thereto. A plurality of microlenses 470 corresponding to color filters 460R, 460G, and 460B can be further provided on color filter layer 460.

[0167] An amorphous boron nitride film 420 may be provided between the color filter layer 460 and the photodiode 450. The amorphous boron nitride film 420, which limits and / or prevents reflection of light entering through the color filter layer 460, may have a low refractive index and high hardness. Since the amorphous boron nitride film 420 is the same as the amorphous boron nitride film described above, its description is omitted.

[0168] When the amorphous boron nitride film 420 is applied as an anti-reflective film to the image sensor 400, the light concentration ratio of each pixel can be improved, and light interference that may occur between pixels can also be limited and / or prevented.

[0169] Figure 20 The lithography apparatus 500 is according to the embodiment.

[0170] refer to Figure 20 The photolithography apparatus 500 may include a substrate 510, a photoresist layer 550 provided on the substrate 510, and an amorphous boron nitride film 520 provided between the substrate 510 and the photoresist layer 550. The substrate 510 may be a structure that will be patterned by the photolithography process.

[0171] The amorphous boron nitride film 520 can limit and / or prevent the reflection of light transmitted through the photoresist layer 550. Since the amorphous boron nitride film 520 is the same as the amorphous boron nitride film described above, its description is omitted. In this embodiment, the amorphous boron nitride film 520 may have a relatively uniform surface to limit and / or prevent scattered reflections. For example, the surface of the amorphous boron nitride film 520 may have a surface roughness of about 0.5 rms or less.

[0172] exist Figure 20 In the state shown, when light of a certain wavelength, such as ultraviolet light, is incident on the photoresist layer 550 through a photomask (not shown), the amorphous boron nitride film 520 effectively restricts and / or prevents the reflection of light transmitted through the photoresist layer 550, thereby precisely patterning the photoresist layer 550 in the desired shape. When the patterned photoresist layer 550 is used as an etching mask to etch the substrate 510, a structure of the desired shape can be achieved.

[0173] In extreme ultraviolet (EUV) or deep ultraviolet (DUV) lithography processes used for ultra-fine integration, a problem arises: as the pattern size decreases, the line edge roughness (LER) or line width roughness (LWR) increases due to light reflection from the patterned substrate. In this embodiment, since an amorphous boron nitride film 520 with a low refractive index and excellent mechanical properties is formed between the substrate 510 and the photoresist layer 550 as an anti-reflective film, ultra-fine patterning can be achieved uniformly and precisely.

[0174] Figure 21 This is a diagram of a solar cell 600 according to an embodiment.

[0175] refer to Figure 21 The solar cell 600 may include a light-absorbing layer 610 and an amorphous boron nitride film 620 provided on the light-absorbing layer 610. The light-absorbing layer 610 may include a semiconductor material that absorbs incident light to generate electrical energy.

[0176] A heat dissipation layer 640 for dispersing heat generated from the light absorption layer 610 may be further provided between the light absorption layer 610 and the amorphous boron nitride film 620, and a transparent substrate 630 may be further provided between the heat dissipation layer 640 and the amorphous boron nitride film 620.

[0177] The amorphous boron nitride film 620 can limit and / or prevent the reflection of incident light, thereby improving the efficiency of the solar cell 600. Since the amorphous boron nitride film 620 is the same as the amorphous boron nitride film described above, its description is omitted. Thus, by forming the amorphous boron nitride film 620 in the solar cell 600, the amount of light incident on the light-absorbing layer 610 can be increased, and the light loss due to reflected light can be reduced.

[0178] Figure 22 This is a diagram of a display device 700 according to an embodiment.

[0179] refer to Figure 22 The display device 700 may include a display panel 710 and an amorphous boron nitride film 720 provided on the display panel 710. Although the display panel 710 may include, for example, a liquid crystal display panel, an organic light-emitting display panel, etc., this disclosure is not limited thereto.

[0180] A transparent substrate 730 may be provided on the upper surface of the display panel 710, and a polarizer 740 for increasing the viewing angle may be provided on the upper surface of the transparent substrate 730. Furthermore, a protective film 750 may be provided on the upper surface of the polarizer 740. An amorphous boron nitride film 720 may be provided as an anti-reflective film on the upper surface of the protective film 750. Since the amorphous boron nitride film 720 is the same as the amorphous boron nitride film described above, its description is omitted.

[0181] The protective film 750 may include a material having a higher refractive index than the amorphous boron nitride film 720. The amorphous boron nitride film 720 may have a refractive index of about 1.0 to about 1.5 in the wavelength range of about 100 nm to about 1000 nm. Although the protective film 750 may have a refractive index greater than, for example, about 1.6, this disclosure is not limited thereto.

[0182] Thus, when the amorphous boron nitride film 720, which acts as an anti-reflective film, is provided on the display panel 710, reflected light reaching the eyes of people viewing the display device 700 can be reduced.

[0183] The above descriptions illustrate examples of amorphous boron nitride films being applied to image sensor 400, photolithography equipment 500, solar cell 600, and display device 700. However, these are merely examples, and the amorphous boron nitride film can be applied to a variety of other devices requiring anti-reflection properties.

[0184] As described above, according to the embodiments, the amorphous boron nitride film can possess the excellent properties required of an antireflective film, such as a low refractive index, excellent thermal, mechanical, and chemical stability, etc. The amorphous boron nitride film can be applied to various devices requiring antireflection. Although embodiments have been described above, these are merely examples, and those skilled in the art to which this disclosure pertains can make various modifications and alterations based on these descriptions.

[0185] It should be understood that the embodiments described herein are to be considered in the descriptive sense only and are not intended for limiting purposes. The descriptions of features or aspects in the various embodiments should be typically considered applicable to other similar features or aspects in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, those skilled in the art will understand that various changes in form and detail may be made therein without departing from the spirit and scope defined by the appended claims.

Claims

1. An amorphous boron nitride film having an amorphous structure, said amorphous structure comprising sp 3 Hybrid bonds and sp 2 Hybridized bonds, wherein sp in the amorphous boron nitride film 3 Hybrid bonds relative to sp 3 Hybrid bonds and sp 2 The ratio of the sum of hybrid bonds is less than 20%, wherein the thickness of the amorphous boron nitride film is 1 / 4 of the center wavelength of the light incident on the amorphous boron nitride film.

2. The amorphous boron nitride film of claim 1, wherein the amorphous boron nitride film has a refractive index of 1.0 to 1.5 for light in the wavelength range of 100 nm to 1000 nm.

3. The amorphous boron nitride film according to claim 1, wherein the atomic ratio of boron to nitrogen in the amorphous boron nitride film is 0.5 to 2.

0.

4. The amorphous boron nitride film as claimed in claim 1, wherein the surface roughness of the amorphous boron nitride film is 0.5 root mean square (rms) or less.

5. The amorphous boron nitride film according to claim 1, wherein the dielectric constant of the amorphous boron nitride film is 2.5 or less.

6. The amorphous boron nitride film of claim 1, wherein the band gap of the amorphous boron nitride film is 6.0 eV or less.

7. The amorphous boron nitride film according to claim 1, wherein the density of the amorphous boron nitride film is 1.8 g / cm³. 3 Or larger.

8. The amorphous boron nitride film as claimed in claim 1, wherein the hydrogen content of the amorphous boron nitride film is less than 10 atoms.

9. An anti-reflective coating structure, including: Substrate, and An amorphous boron nitride film as described in any one of claims 1-8 on the substrate.

10. The antireflective coating structure as claimed in claim 9, further comprising: At least one material layer between the substrate and the amorphous boron nitride film.

11. The antireflective coating structure of claim 10, wherein the at least one material layer has a refractive index greater than that of the amorphous boron nitride film.

12. An image sensor, including: Substrate; Multiple photodiodes in two-dimensional form on the substrate; Color filter layer on the plurality of photodiodes; as well as The amorphous boron nitride film as described in any one of claims 1-8 on the plurality of photodiodes.

13. The image sensor of claim 12, wherein the amorphous boron nitride film is located between the plurality of photodiodes and the color filter layer.

14. The image sensor of claim 12, further comprising: Multiple microlenses in two-dimensional form on the color filter layer.

15. Photolithography equipment, including: Substrate; A photoresist layer on the substrate; as well as An amorphous boron nitride film as described in any one of claims 1-8, located between the substrate and the photoresist layer.

16. Solar cells, including: A light-absorbing layer that absorbs incident light and generates electrical energy; and The amorphous boron nitride film as described in any one of claims 1-8 on the light-absorbing layer.

17. The solar cell of claim 16, further comprising: A heat dissipation layer between the light-absorbing layer and the amorphous boron nitride film.

18. A display device, including: Display panel; as well as The amorphous boron nitride film as described in any one of claims 1-8 on the display panel.

19. The display device of claim 18, further comprising: A protective film between the display panel and the amorphous boron nitride film.

20. The display device of claim 19, wherein the refractive index of the protective film is greater than the refractive index of the amorphous boron nitride film.

Citation Information

Patent Citations

  • Novel sp2-sp3 hybridized crystalline boron nitride and preparation method thereof

    CN113526475A